Sintesis Tiga Peptida Bergugus Pelindung sebagai Prekursor Komponen Vaksin Influenza Universal - Subroto, Toto; Hardianto, Ari; Kahari, Abdul Alim; Pradnjaparamita, Tika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Current highly effective conventional vaccine to halt the spread of bird flu has not been invented yet because of susceptiblemutation of influenza virus. In spite of undergoing mutation which causes the amino acid sequence change, influenzaviruses maintain conservation at ectodomain of M2 protein, especially M2e(2-16) (SLLTEVETPIRNEW). The use ofconserved epitope M2e(2-16) in epitope-based vaccine potentially produces universal influenza vaccine. In designingepitope-based vaccine, the M2e(2-16) needs to be coupled with T helper epitope, P25, which is subsequently mentioned asM2e(2-16)-K-P25 (SLLTEVETPIRNEWGKKKL IPNASLIENCTKAEL). The M2e(2-16)-K-P25 was synthesized usingconvergent solid phase peptide synthesis strategy because of the size of the sequence. In this strategy, four peptideprecursors of M2e(2-16)-K-P25; SLLTEVETP (F1), IRNEWGK (F2), KLIPNASLI (F3), and ENCTKAEL (F4); were synthesizedin advance. After the precursors ready, coupling reaction was performed to obtain M2e(2-16)-K-P25. In the previousresearch, F3 has been obtained in high purity through Fmoc/tBu solid phase peptide synthesis method. In this conductedresearch, the three remaining precursors; F1, F2, and F4; were synthesized by the same method. Each peptide was analysedby thin layer chromatography, HPLC, and mass spectroscopy methods. F1, F2 and F4 were successfully synthesized andeach of them was detected at 1490.0, 1874.8 and 1881.9 amu, respectively. However, F1 was not possible to purify becauseof its insolubility in various solvents.